(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the immediate effect of different drying temperatures on the nutritional quality of beans cultivar BRS Estilo. Harvesting and screening were carried out manually, after selecting the grains, the moisture content of 20 ± 0.5% (wet basis) was determined. The grains were submitted to the drying process, in an experimental horizontal fixed layer dryer with forced ventilation at temperatures of 40, 50, 60 and 70 ºC, until reaching the final moisture content of 11 ± 0.3% (wet basis). In order to carry out nutritional analyzes, the beans were ground into flour and sieved through a 50 mesh sieve. Nutritional quality was assessed through its nutritional composition, considering the levels of minerals (Fe, Zn, Mn, Cu, Ca, Mg, K, P), crude protein, ether extract, carbohydrates, crude fiber and ashes, all performed in triplicate, each with two repetitions. Based on the results, it was possible to conclude that: the mineral content, as well as the total fiber and ash contents were not influenced by the drying temperature and higher drying temperatures provided statistically significant lower levels of proteins and lipids.